2020
DOI: 10.1177/2041419620911133
|View full text |Cite
|
Sign up to set email alerts
|

Approximating a far-field blast environment in an advanced blast simulator for explosion resistance testing

Abstract: While the current state of blast-resistant design methods is based largely on empirical observations of actual explosive testing or numerical simulations, experimental testing remains the ultimate method for validating blast protection technologies. Field trials for performing systematic experimental studies are exceedingly expensive and inefficient. Conventional blast simulators (shock tubes) enable blast testing to be performed in a safe and controlled laboratory environment but are significantly deficient. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Second, the Friedlander wave-shape was used to define the shock wave. The wave shape has been found to match experimental data 18 and over-estimate pressures in the tail of the shock wave at pressures below 50% of the peak 71 . Third, the analysis is based on TNT explosions of an armored passenger-vehicle and ground personnel.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Second, the Friedlander wave-shape was used to define the shock wave. The wave shape has been found to match experimental data 18 and over-estimate pressures in the tail of the shock wave at pressures below 50% of the peak 71 . Third, the analysis is based on TNT explosions of an armored passenger-vehicle and ground personnel.…”
Section: Discussionmentioning
confidence: 64%
“…Several sources were used to tabulate the shock wave characteristics. Most of the results have been confirmed against testing from low-weight to nuclear explosions, although caution has been raised that not all parameters are accurately determined by the empirical relationships for small Z 16 , 18 .…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Barik et al (2020) used a shock tube and studied the effect of bending pre-strain and pressure on the forming behavior of AA5052−H32 sheets. Gan et al (2020) demonstrated the advanced blast simulator that could generate a far-field blast environment accurately and suit high-precision and repeatable explosion testing of various building components. Kochavi et al (2020) designed a blast simulator that could simulate the damage to biological models from the blast environment generated by 3.5 kg of spherical TNT.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of the economy, many important economic facilities are threatened by accidental explosions and terrorist attacks [ 3 ]. The shock tube is a device that can be used to simulate blast waves, which can test most materials and engineering structures [ 4 , 5 , 6 , 7 , 8 ]. Therefore, investigating the overpressure fields in shock tubes has important engineering significance.…”
Section: Introductionmentioning
confidence: 99%